1981
DOI: 10.1007/bf01318135
|View full text |Cite
|
Sign up to set email alerts
|

The role of carbohydrate in determining the immunochemical properties of the hemagglutinin of influenza A virus

Abstract: Most of the carbohydrate was removed from influenza virus MRC II (H3N2) and its purified hemagglutinin (HA) on treatment with glycosidases, including alpha-mannosidase, beta-N-acetylglucosaminidase, beta-galactosidase and alpha-fucosidase. The release of 50 per cent of the carbohydrate from intact virus particles significantly affected hemagglutinating activity. The ability of untreated and glycosidase-treated virus to inhibit the binding of antibodies directed against the hemagglutinin was almost indistinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Carbohydrate moieties of glycoproteins are known to play different roles in intracellular routing (6), protection of the molecule against proteolytic degradation (7), governing correct folding and stabilizing bioactive conformation of the molecule (7), or as epitopes for antibody immune responses (8,9). Carbohydrates are also involved in the regulation of molecular metabolism (10)(11)(12), growth and differentiation (11,13), and in cell-to-cell adhesion (14,15).…”
mentioning
confidence: 99%
“…Carbohydrate moieties of glycoproteins are known to play different roles in intracellular routing (6), protection of the molecule against proteolytic degradation (7), governing correct folding and stabilizing bioactive conformation of the molecule (7), or as epitopes for antibody immune responses (8,9). Carbohydrates are also involved in the regulation of molecular metabolism (10)(11)(12), growth and differentiation (11,13), and in cell-to-cell adhesion (14,15).…”
mentioning
confidence: 99%
“…So far, these epitopes seem to be unique among viral glycoproteins as their reactivity is lost after treatments removing only a small fraction of the carbohydrate content. Carbohydrate-dependent epitopes have been demonstrated previously for glycoproteins of other viruses such as Newcastle disease virus (Merz et al, 1981, Long et al, 1986, Semliki Forest virus (Kaluza et al, 1980) and influenza virus (Gitelman et al, 1981;Hongo et al, 1986). However, the carbohydrate dependence of these epitopes was detected in glycoprotein produced in the presence of tunicamycin, resulting in a completely non-glycosylated protein (Long et at., 1986;Kaluza et al, 1980) or in extensively glycosidase-treated glycoproteins (Gitelman et al, 1981).…”
Section: Discussionmentioning
confidence: 77%
“…GIWSr,MA~ et al (7) have analysed the antigenicity of influenza A virM HA proteins by competitive radioimmunoassay before and after glycosidase treatment, and have demonstrated a significant decrease in the antigenicity of HA after removal of more than 50 per cent of carbohydrates. Immunopreeipitation experiments revealed that of the three monoclonal antibodies tested, two antibodies designated S-i6 and J-6 reacted with both the gp 88 and T 76 polypeptides, indicating that some of the antigenic determinants on gp88 molecules can be expressed even in the absence of gtycosylation.…”
Section: Diseussionmentioning
confidence: 99%
“…It has been reported that the antigenicity of either gp71 of Friend marine leukemia virus or gp85 of avian sarcoma virus (B77) remained intact even after the removal of most carbohydrates by digestion with a mixture of highly purified glycosidases (22,26). G[TELMAN et al (7) have also demonstrated that the antigenicity of influenza A viral hemagglutinin (HA) was significantly reduced after glycosidase treatment. G[TELMAN et al (7) have also demonstrated that the antigenicity of influenza A viral hemagglutinin (HA) was significantly reduced after glycosidase treatment.…”
Section: Introduetionmentioning
confidence: 99%